TIME LAG BETWEEN CATCHING AND CURING OF FISH AND ITS INFLUENCE ON THE FINISHED PRODUCT 1. MACREL - UNNIKRISHNAN NAIR, T S; VALSAN, A P (Fishery Technology, 2025)
A study is made to determine the maximum permissible time lag both under iced and uniced storage conditions between the catching of mackerel (Rastre!liger k.anagurta) and its curing, so that the quality of the finished product is within tolerable limits. Based on physical, chemical, bacteriological and taste panel studies the maximum time lag permissible is fixed as 3 brs under unliced condition and 3 days under iced condition. Icing of fish is also found to affect the tasting qualities of the finished product.